Spontaneous Regression of Epstein‐Barr Virus‐negative Diffuse Large B‐cell Lymphoma that Presented with Multiple Pulmonary Nodules. (27th September 2016) - Saraya, Takeshi; Tsujimoto, Naoki; Tamon, Hiroki; Nunokawa, Hiroki; Ohkuma, Kosuke; Tsukahara, Yayoi; Fujiwara, Masachika; Ishii, Haruyuki; Takizawa, Hajime
Abstract : A 70‐year‐old woman was admitted to a respiratory department because of bilateral inguinal lymphadenopathy, mediastinal lymphadenopathy, and re‐growth of a nodule in the left lower lobe, which had been identified one year earlier but had regressed spontaneously over the next 6 months. After diagnostic procedures to obtain tissue from the lung and lymph nodes, she was diagnosed with Epstein‐Barr virus‐negative diffuse large B‐cell lymphoma (DLBCL). Spontaneous regression or remission of lung involvement in a patient with DLBCL has rarely been reported and the precise mechanism is unknown, but this case clearly demonstrated regression and re‐growth of the lung nodules during her clinical course.